2014
DOI: 10.1089/ars.2013.5341
|View full text |Cite
|
Sign up to set email alerts
|

Role of Heme Oxygenase-1 in Postnatal Differentiation of Stem Cells: A Possible Cross-Talk with MicroRNAs

Abstract: Significance: Heme oxygenase-1 (HO-1) converts heme to biliverdin, carbon monoxide, and ferrous ions, but its cellular functions are far beyond heme metabolism. HO-1 via heme removal and degradation products acts as a cytoprotective, anti-inflammatory, immunomodulatory, and proangiogenic protein, regulating also a cell cycle. Additionally, HO-1 can translocate to nucleus and regulate transcription factors, so it can also act independently of enzymatic function. Recent Advances: Recently, a body of evidence has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 256 publications
(386 reference statements)
2
36
0
Order By: Relevance
“…176 For example, expression of HO-1 in myoblasts downregulated specific miRs ( e.g., miR-1, miR-133a/b, and miR-206) associated with the inhibition of myoblast differentiation. 177 Expression of HO-1 in tumor cells was associated with downregulation of miR-378.…”
Section: Regulation Of Heme Oxygenase Gene Expressionmentioning
confidence: 99%
“…176 For example, expression of HO-1 in myoblasts downregulated specific miRs ( e.g., miR-1, miR-133a/b, and miR-206) associated with the inhibition of myoblast differentiation. 177 Expression of HO-1 in tumor cells was associated with downregulation of miR-378.…”
Section: Regulation Of Heme Oxygenase Gene Expressionmentioning
confidence: 99%
“…13 In addition, HO-1 expression is also regulated in a posttranscriptional manner by miRNAs. 14 Indeed, studies performed in the context of an intravascular hemolysis model, showed that miR-377 and miR-217 interact with the Hmox1e3 0 -untranslated region, resulting in the reduction of HO-1 protein expression and, hence, reduced enzymatic activity. 15 Furthermore, miR-122, which is a miRNA highly expressed in the human liver, also down-regulates HO-1 expression.…”
Section: Regulation Of Ho-1 Expressionmentioning
confidence: 99%
“…This study demonstrated that CO-mediated mitochondria biogenesis is a crucial step in the maturation of embryonic stem cells into energetically efficient cardiomyocytes, 202 providing additional evidence on the emerging and perhaps crucial role of the HO-1 pathway in the control of energetic metabolism not only in cardiac tissue but also during stem cell differentiation. 203 …”
Section: Future Exploitation Of Ho-1/co As Protective Therapies In Thmentioning
confidence: 99%